Studying the Stability of the ψ-Hilfer Fractional Differential System - Jinping Yang; Zhiqiang Li (Complexity)
This paper devotes to the study on the stability and decay of solution to fractional differential system involving the ψ-Hilfer fractional derivative of order α∈0,1 and type β∈0,1. We first derive the solution of linear system by using the generalized Laplace transform, which can be represented by the form of Mittag-Leffler function. Then, in terms of the asymptotic expansion of the Mittag-Leffler function, stability properties of linear system are analyzed in more detail. Finally, we construct a linearization theorem and determine the stability near the equilibrium for the autonomous nonlinear differential system with the ψ-Hilfer derivative.